META ANALISIS PENGARUH PENGGUNAAN E-BOOK TERHADAP HASIL PEMBELAJARAN IPA - Ni Putu Apriantini; A.A. Istri Agung Rai Sudiatmika (PGSD UNIKA SANTU PAULUS RUTENG, 2024)
This research uses a meta-analysis method using qualitative descriptive analysis to determine the effectiveness of a learning media, namely the use of E-Books, on science learning outcomes at junior high school level. The sample of journals used for analysis were 8 national journals that were relevant to the research. The journals used are composed of units of analysis, namely: 4 junior high school class VII journals; 3 junior high school (Junior High School) class VIII journals and 1 class IX junior high school journal and accessed online using one of Google Scholar's online media which contains journals from the last 10 years (2013 to 2023). The results of meta-analysis research show that the use of E-Book learning media can improve student learning outcomes in science learning. This can be seen through the lowest percentage of learning outcomes of 7% and the highest increase of 47.59% and has an effect size value of 1.42, so it can be concluded that E-Book learning media has a great influence on learning outcomes.